Reconstruyendo la historia: Posmemoria y literatura ectópica - Luarsabishvili, Vladimer (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This paper deals with the possible ways of understanding the relation between the reconstruction of history and literary fiction (postmemory and ectopic literature). The transmission of memory across generations – postmemory, and the composition of literary works out of the place of the origin – ectopic literature – facilitate the formation of historical discourse, which is inevitably accompanied by modern interpretation. As interpretation is understanding reality in a subjective manner, literary fiction takes its place in the reconstruction of historical events. And ectopic literature is one of the main narratives, which helps to understand the relation between facts and fantasy.
Keywords: historia; posmemoria; narrativa; literatura ectópica